2016
DOI: 10.1186/s12944-016-0193-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary n-6/n-3 polyunsaturated fatty acid ratios on boar reproduction

Abstract: BackgroundN-3 and N-6 polyunsaturated fatty acids are widely used in reproduction, yet few studies have addressed the effects of dietary n-6/n-3 ratios on boar reproduction. The present study aimed to determine the effects of different dietary n-6/n-3 ratios on the reproductive performance ofn breeding boars. Thirty-two boars with body weights of 15.0 ± 1.4 kg were divided into four treatments (C, T1, T2, T3) and fed diets with different n-6/n-3 fatty acid ratios (29.06:1, 20.07:1, 1:1, 1:17.96, respectively) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…Various researchers have used different periods of supplementation with PUFAs, such as 60 days (stallions), 16 weeks (boars), 30 weeks (stallions) and 174 days (boars) (Freitas et al, ; Lin et al, ; Liu et al, ; Rodrigues et al, ). We believe our experiment is the first assessing the possible alterations at 60 days after the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers have used different periods of supplementation with PUFAs, such as 60 days (stallions), 16 weeks (boars), 30 weeks (stallions) and 174 days (boars) (Freitas et al, ; Lin et al, ; Liu et al, ; Rodrigues et al, ). We believe our experiment is the first assessing the possible alterations at 60 days after the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 However, other experiments supplementing boar diets with PUFAs ω-3 and ω-6 improved the quality of seminal characteristics, modifying the fatty acid composition of the sperm. 1,6,7 Although seminal characteristics were not affected by CLA intake during the experimental period, the increase in sperm concentration and viability and the decrease in abnormal morphology may be related to seasonal changes in temperature. Previous studies performed in colder months suggested that during the cooler months of the year, sperm count and semen production improved, 37 and sperm abnormalities were fewer in pigs housed in cool temperatures.…”
Section: Original Researchmentioning
confidence: 92%
“…5 Specifically, pigs are effective in transferring fatty acids from the diet to the germ cells. 6,7 Previous studies found that the fatty acid composition of sperm was modified with PUFAs supplementation 6,8,36 , suggesting that PUFAs supplementation changes the lipid composition of the semen of boars. However, our results were contrary to these findings, and these differences may be due to the breeds used in the experiments.…”
Section: Fatty Acid Profile In Sperm Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oils that are rich in n-3 PUFAs also significantly increased sperm density and sperm number [57] . Lin et al [58] determined the effects of different dietary n-6/n-3 ratios on the reproductive performance of breeding boars and found that proper n-6/n-3 PUFAs ratio in the diet of breeding boars enhanced the development of testis and accessory sex gland function, and improved sperm quality, which may be related to favorable hormone metabolism and antioxidant capacity.…”
Section: Boar Nutritionmentioning
confidence: 99%